The sun and the scythe: energy dispossessions and the agrarian question of labor in solar parks. Issue 5 (29th July 2021) - Stock, Ryan; Birkenholtz, Trevor
ABSTRACT: Green grabbing is accelerating throughout the Global South to facilitate climate change mitigation. This paper illuminates the discursive and extra-economic means through which the state dispossesses agropastoralists of both land and energy to develop solar parks in semi-arid rural India. We advance the empirical and theoretical aspects of energy dispossessions, with implications for the agrarian question of labor. Using data obtained from mixed methods fieldwork, this research reestablishes the urgency of responding to the classical agrarian question in the context of low-carbon energy transitions.